1990
DOI: 10.1111/j.1476-5381.1990.tb12092.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peptidase inhibitors on bradykinin‐induced bronchoconstriction in guinea‐pigs in vivo

Abstract: 1 Bradykinin (BK) instilled directly into the airway lumen caused bronchoconstriction in anaesthetized, mechanically ventilated guinea-pigs in the presence of propranolol (1 mg kg-i.v.) The geometric mean dose of BK required to produce 100% increase in airway opening pressure (PD100) was 22.9 nmol (95% c.i. 11.7-44.6 nmol). 2 The dose-response curve for the effect of instilled BK was significantly shifted to the left by the angiotensin converting enzyme (ACE) inhibitor, captopril (5 and 50nmol instillation, PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 20 publications
0
15
2
Order By: Relevance
“…This contrasts with observations made in anesthetized guinea pigs where intravenous (Ichinose and Barnes, 1990a;Wirth et al, 1993;Tramontana et al, 2001), intratracheal (Ichinose and Barnes, 1990b), or inhaled (Sakamoto et al, 1994) bradykinin exerted bronchoconstriction. The lack of effect of inhaled bradykinin in conscious guinea pigs seems to be caused by the rapid breakdown of bradykinin because there was a significant bronchoconstriction after treatment with captopril, an ACE inhibitor.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This contrasts with observations made in anesthetized guinea pigs where intravenous (Ichinose and Barnes, 1990a;Wirth et al, 1993;Tramontana et al, 2001), intratracheal (Ichinose and Barnes, 1990b), or inhaled (Sakamoto et al, 1994) bradykinin exerted bronchoconstriction. The lack of effect of inhaled bradykinin in conscious guinea pigs seems to be caused by the rapid breakdown of bradykinin because there was a significant bronchoconstriction after treatment with captopril, an ACE inhibitor.…”
Section: Discussioncontrasting
confidence: 52%
“…NEP is expressed in the respiratory epithelium (Baraniuk et al, 1995), so inhalation exposure would enable phosphoramidon to have an instant effect, whereas after intraperitoneal injection the drug may not be reaching the lung in a concentration sufficient to inhibit NEP. Captopril and phosphoramidon were shown to potentiate the bronchoconstriction by airway-instilled bradykinin in anesthetized guinea pigs (Ichinose and Barnes, 1990b) and intravenous (Chodimella et al, 1991). The kininase I inhibitor DL-2-mercaptomethyl-3-guanidinoethylthiopropionic acid (MGTA) failed to alter the bronchoconstriction in both of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…NK receptor-dependent axonal reflexes may also contribute to the airway responses evoked by bradykinin in guinea pigs (Nakajima et al, 1994;Joad et al, 1997). However, we observed that drugs that prevent bradykinin-induced bronchospasm did not prevent bradykinin-induced coughing, while drugs that would be expected to enhance bradykinin-induced bronchospasm (e.g., captopril, L-NNA, and thiorphan) (Ichinose and Barnes, 1990;Ricciardolo et al, 1994b) did not, on their own, enhance bradykinin-evoked coughing.…”
Section: Discussioncontrasting
confidence: 50%
“…In experiments with bradykinin, all animals were pretreated with captopril (5mg kg 1) 15min before the beginning of the experiment to block bradykinin metabolism (Ichinose & Barnes, 1990a) and potentiate its effects.…”
Section: Measurement Ofairway Resistancementioning
confidence: 99%